The effects of pollution on the vitamins A, E, C, ?-carotene contents and oxidative stress of the freshwater crayfish, Astacus leptodactylus - Barim, Ozden; Karatepe, Mustafa (Academic Press Inc Elsevier Science, 2010)
In this study, we determined the effects of pollution on levels of antioxidant vitamins (A, E, C), beta-carotene and malondialdehyde (MDA), in the hepatopancreas and muscle tissues of freshwater crayfish (Astacus leptodactylus). The crayfish samples were collected from Aydincik (unpolluted control site) and Agin (polluted site) in the Keban Dam Lake (Elazig-Turkey) in August 2007. The results showed that the concentrations of vitamins E, C and beta-carotene in both tissues were significantly lower, and MDA levels were higher than in controls. There were no significant alterations in vitamin A levels. In comparison among the sex groups, some values were different significantly between the localities. The comparison of same-sex groups of the different localities also showed that concentrations of the vitamins E, C, beta-carotene and MDA changed statistically according to the tissues between the localities. (C) 2009 Published by Elsevier Inc.
Keywords: Astacus leptodactylus; Pollution; Vitamins; beta-carotene; Oxidative stress; Sex